The neighbourhood facilities and the sustainable communities agenda:an overview - Kasim, Rozilah (2007)
Neighbourhood may influence the community sustainability in many ways. Investing in housing alone without providing for the quality of neighbourhood facilities would waste money and potentially lead to social problem. Agenda 21 recognises that communities were at the core of the sustainability. The Malaysian government also recognises the importance of the sustainability as part of its agenda in improving the well being of all Malaysians. The 9MP and the 2008 budget reports strongly emphasise on the improvement of the standard and sustainability of quality of life for the communities. This evidence puts the communities at a centre of the programme. However, the reports do not specifically address who are the stakeholders that are involved in the delivery process and how the community sustainability should be delivered. This paper focuses on the role of neighbourhood facilities within the context of supporting and sustaining the existing communities. It discusses the present understandings of the sustainable communities’ practices and how far these fit within neighbourhood facilities thinking in housing developments. The most likely outcome of this approach is the deprofessionalisation of skills towards community-based approach in meeting those objectives. The paper builds on established literature and generates debate on the role of neighbourhood facilities in creating sustainable communities within the Malaysia context.